Melintasi Budaya: Proses Adaptasi Migran Flores di Bali - Sunaryo, Fransiska Dewi Setiowati; Wahyuni, Anak Agung Ayu Rai; Wahyuni, Anak Agung Ayu Rai (Prosiding Seminar Nasional Sains dan Teknologi (Senastek), 2024)
Since Indonesia's independence, migrants from outside the island of Bali began to arrive, not only from Java, Madura, and Lombok but also from East Nusa Tenggara, namely Flores. The economic conditions and limited job opportunities in Flores are factors that encourage them to migrate to the surrounding areas that are more developed. Bali is one of the destination areas because of the pull factor of tourism and development that requires informal labor from outside Bali. They mostly work in the construction and tourism services sectors. The increasing number of migrants coming to Bali has positive implications and creates population problems that cannot be avoided. For this reason, this study examines how the challenges of Flores migrants and their struggles to be accepted and survive in Bali, which is predominantly different in terms of social, cultural, and economic aspects. This research uses qualitative methods with the concepts of migration ethnicity and identity. Data were collected through six-month observation, in-depth interviews with Flores migrants and Flobamora community leaders and local people, and a literature study. The results of the study show that Flores ethnic migrants in Bali can survive with local identity while adapting to the local culture in Bali.